In-service mathematics teachers’ knowledge of differentiated instruction - Patrick Kyeremeh; Nixon Saba Adzifome; Emmanuel Kojo Amoah (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2022)
This study sought to investigate in-service mathematics teachers’ knowledge of differentiated instruction in junior high schools in Tano South Municipality of Ghana. The study adopted an explanatory sequential mixed method design. We employed a sample of 50 JHS mathematics teachers comprised 41 general in-service teachers and 9 special in-service teachersin the quantitative study through proportionate stratified sampling technique. In the qualitative phase, 6 JHS mathematics teachers comprising 4 general in-service teachers and 2 special in-service teachers were purposively selected and interviewed. In line with the design adopted, the quantitative data obtained through questionnaire was first collected and analysed. This was followed by the qualitative data obtained through semi-structured interviews. The quantitative data were analysed using both descriptive statistical tools (such as frequency counts, percentages, mean, standard deviation and average per item rating), and inferential statistical tool (independent samples t-test). Qualitative data used inductive content analysis. Among the findings, we found no statistically significant difference in the knowledge scores on differentiated instruction for general in-service teachers and special in-service teachers (t = -0.80, df = 48, p 0.05). We therefore recommend teacher education institutions to review their mathematics curriculum to reflect the use of differentiated instructional approaches among mathematics teachers.